Equity in access to COVID-19 testing for undocumented migrants and homeless persons during the initial phase of the pandemic - Stephanie Baggio; Frederique Jacquerioz; Julien Salamun; Hervé Spechbach; Yves Jackson (Elsevier, 2021)
Introduction: The COVID-19 pandemic has excessively affected socially and economically deprived groups of population. There is a dearth of empirical evidence about the effect of policies regulating access to care for such groups. This study aims to document the impact of an equity-based strategy to facilitate access to COVID-19 testing during the initial phase of the pandemic. Materials and methods: This cross-sectional study included all outpatients presenting at the Geneva University Hospital for COVID-19 testing in March and April 2020. We compared the testing program uptake, and the proportions of positive tests and of complicated clinical course between undocumented migrants and homeless persons and the general population. Results: Underserved patients represented 215 (6.5%) of the 3299 participants. There was no significant difference in the time-lag between the first COVID-19 evocative symptoms and the testing, the number of symptoms at presentation, and the participation to the program during its first month of implementation. The proportion of positive tests was significantly higher (32.1% vs. 23.6%, p=.005) among undeserved while the proportion of complicated clinical course was comparable. Conclusions: Equity-based policies can mitigate disparities in access to care during the pandemic and reduce the spread of COVID-19 in the community by early detection of infective cases. The high proportion of positive test in underserved patients highlight the need to include such groups into future COVID-19 immunization program. More globally, this study highlights the opportunity to reinforce healthcare systems to adapt to new threats and to contribute to a better protection of the whole of society.